Conservative management of type II and III odontoid fractures in the elderly at a regional spine centre: A prospective and retrospective cohort study. (April 2015) - Patel, Amit; Zakaria, Rasheed; Al-Mahfoudh, Rafid; Clark, Simon; Barrett, Chris; Sarsam, Zaid; Pillay, Robin; Pigott, Tim Drummond; Wilby, Martin J.
Abstract Background. The optimal management of odontoid fractures in the elderly population is unclear and management of this group of patients is complicated by multiple co-morbidities. This study aimed to determine the outcomes after conservative management strategies were applied in this patient group. Methods. We carried out retrospective and prospective analyses of all patients with axial cervical spine injuries, at a single centre. We included patients aged over 60 years with type II and III odontoid fractures. Information was gathered on demographics, ASA grading-associated injuries and complications. The outcome measures were rates and type of union, pain and neurological functions, specifically ambulation. Results. Fifty-seven adult patients with a median age of 78 years (range 60–92 years) were included. There were 42 type II and 15 type III odontoid fractures. Three patients required surgical fixation due to displaced fractures, which could not be reduced with manual traction. Twenty-four (41%) patients were managed with a rigid pinned halo orthosis to obtain adequate reduction and immobilisation. The remaining 30 (53%) were managed in a hard cervical collar. Patients managed with a halo were significantly younger and had more associated injuries than patients managed in a collar (age: t-test = 4.05, p < 0.01, associated injuries: Chi-square = 4.38, p < 0.05). At a mean follow-up of 25 weeks, 87% of type II and 100% of type III fractures had achieved bony union or stable, fibrous non-union. There were no statistical differences in fracture type, follow-up or neurological outcomes between the halo and collar groups. However, overall more patients managed in a collar developed stable fibrous non-union than bony fusion (Fisher's exact test, p < 0.05), although this was not significant when analysed by each fracture type individually. A regression model was constructed and identified fracture type as the only independent predictor of time to union, with type III fractures healing faster than type II. Conclusions. High rates of bony union and stable fibrous non-union with a good functional outcome can be achieved in the elderly population sustaining type II or III odontoid fractures, when managed non-surgically. Halo orthosis may not offer any clear advantage over hard collar in this group. Close follow-up is needed for late complications and there must be a willingness to perform surgery if conservative measures fail.